Weight Change–Adjusted Effects of Gastric Bypass Surgery on Glucose Metabolism: 2- and 10-Year Results From the Swedish Obese Subjects (SOS) Study - Sjöholm, Kajsa; Sjöström, Elisabeth; Carlsson, Lena M.S.; Peltonen, Markku (Diabetes care, 2016)
It has been suggested that weight change-independent effects on fasting insulin and glucose levels are present after gastric bypass (GBP) but not after banding and vertical banded gastroplasty (VBG). We therefore evaluated weight change-adjusted effects of GBP, compared with restrictive surgical procedures, on long-term changes in fasting levels of glucose, insulin, and homeostatic model assessment of insulin resistance (HOMA-IR) in the Swedish Obese Subjects (SOS) study. Participants who completed the 2-year (n = 1,762) and/or the 10-year (n = 1,216) follow-up were divided into three weight change classes (weight loss >30%, 20-30%, or ≤20%), and by surgical method (banding, VBG, or GBP). Glucose, insulin, and HOMA-IR changes were analyzed in relation to weight change over 2 and 10 years. Analyses were performed in the full cohort and also in subgroups based on baseline glucose status. Within weight change classes, reductions in glucose, insulin, and HOMA-IR were similar in the three surgery groups both at 2 and at 10 years. Reductions in glucose, insulin, and HOMA-IR increased with increasing weight loss, and changes were typically related to weight change within each surgery group. Moreover, the association between weight change and change in glucose, insulin, or HOMA-IR did not differ between the surgery groups at 2 and 10 years. When patients were subdivided also by baseline glucose status, similar relationships between weight changes and changes in glucose, insulin, and HOMA-IR were observed. Even though weight loss-independent effects are important for short-term diabetes remission, our results suggest that degree of weight loss is more important for long-term reductions in fasting insulin and glucose than choice of bariatric surgery procedure.